Applying Artificial Intelligence (AI) in Sayembara 2024 Art Exhibition from textual to visual - Bebit, Mohd Ali Azraie; Mohamad Khalil, Musaddiq; Jaapar, Iqbal; Amairudin, Muhammad Firdaus; Samar, Amir Nor Azan (Faculty of Art and Design, 2025)
The Malaysian Budget 2025 was announced by Malaysia’s 10th Prime Minister, who allocated almost RM50 million towards the development of language and literature. Through such commitment provided by the Madani framework government, the National Art Gallery (NAG) launched an art project entitled Sayembara 2024. This art project is the first of its kind, focusing on 13 public and private higher education institutions. Sayembara is a competition exhibition that selects artworks from institutions and, in collaboration with Gamuda Mall Bukit Bintang (GMBB), displays artworks to the public. Interestingly, the concept was to interpret the masterpiece text into the visual works of art. UiTM Melaka chose the Sulalatus Salatin text from the Malay Annals. The process started by selecting two works of representational and non-representational (abstract) are selected as results from the Gallery Art Studio (GAS) UiTM Melaka, listed by the NAG Curators. Based on the 2 artworks, this study seeks to investigate the role of Artificial Intelligence (AI) generators in producing artworks and how they can contribute to cultural expression. The findings proved that AI image generators play a significant role in the preliminary process of art making. However, the overall cultural expression and artwork produced must be verified through further steps, which are controlled by the artist's involvement and understanding of his/her reality where they find themselves. The results and findings generated possibilities for future researchers and visual artists upon investigating more on the role of AI and cultural expression.